Characteristics of community acquired and hospital acquired methicillin resistant Staphylococcus aureus isolates in the National Hospital of Sri Lanka - WAMP Samaranayake; L Karunanayake; CGUA Patabendige (Sri Lankan Journal of Infectious Diseases, 2019)
Introduction and Objectives: Highly virulent community acquired methicillin resistant Staphylococcus aureus (MRSA) strains emerged recently causing infections in healthy young adults without predisposing factors. This descriptive cross-sectional study was conducted to compare socio-demography of patients and microbiology and molecular characteristics of Community acquired (CA) and Hospital acquired (HA) methicillin resistant S. aureus strains isolated at the National Hospital of Sri Lanka. Methods and Results: Antimicrobial susceptibility test and Panton Valentine Leukocidine (PVL) gene detection was carried out on 100 MRSA isolates. CDC epidemiological criteria were used for differentiation of CA and HA MRSA. Of those 100 isolates, 21(21%) were CA-MRSA and 79(79%) were HA-MRSA. Patients did not show any significant difference in acquiring CA MRSA and HA MRSA in relation to their age, sex and gender except ethnicity. The majority of these isolates were from pus samples. CA-MRSA isolates were significantly more sensitive to ciprofloxacin, fusidic acid, tetracycline, cotrimoxazole, and gentamicin compared with HA-MRSA isolates (p<0.001). Inducible, constitutive clindamycin resistance (p<0.001) and multidrug resistant phenotypes were significantly higher (p<0.001) among patients with HA-MRSA infection. All isolates were susceptible to glycopeptides, rifampicin and linezolid. Mupirocin resistance was seen in 6% and all isolates came from patients who harboured HA-MRSA strains (p<0.338). The PVL gene (P<0.001) was present in 20 (95.2%) of CA-MRSA isolates. Conclusion: This study highlights the importance of accurate differentiation of CA and HA MRSA using epidemiological, microbiological and molecular characteristics. Further, awareness of the existence of these types will optimise individual treatment strategies.